Cochrane Database of Systematic Reviews 2003
DOI: 10.1002/14651858.cd000284
|View full text |Cite
|
Sign up to set email alerts
|

Chlorpromazine versus placebo for schizophrenia

Abstract: Background Chlorpromazine, formulated in the 1950s, remains a benchmark treatment for people with schizophrenia. Objectives To review the effects of chlorpromazine compared with placebo, for the treatment of schizophrenia. Search methods We searched the Cochrane Schizophrenia Group's Trials Register (15 May 2012). We also searched references of all identified studies for further trial citations. We contacted pharmaceutical companies and authors of trials for additional information. Selection criteria We includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
3

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 319 publications
1
33
0
3
Order By: Relevance
“…The weight gain reported by [18] was observed in animals in the control groups. The low dose treatment animals show a negligible weight loss while the high dose treatment animals showed an appreciable loss in weight.…”
Section: Discussionmentioning
confidence: 85%
“…The weight gain reported by [18] was observed in animals in the control groups. The low dose treatment animals show a negligible weight loss while the high dose treatment animals showed an appreciable loss in weight.…”
Section: Discussionmentioning
confidence: 85%
“…62 For example, 39% of people diagnosed with schizophrenia do not respond after up to 8 weeks of chlorpromazine treatment. 63 Patients who are resistant to treatment should be distinguished from those who initially respond to treatment and then deteriorate. CT or MRI scanning may be used in these situations to determine whether an intra-cranial lesion may be a cause of treatment resistance.…”
Section: Management Of Psychosismentioning
confidence: 99%
“…The four Cochrane reviews 4,5,13,14 that had already been completed before the commencement of this review were assessed for aspects of methodological quality. All four clearly set out inclusion criteria for studies but some may have been a little too inclusive.…”
Section: Quality Of Existing Cochrane Reviews and Ease Of Usementioning
confidence: 99%
“…About 30% of individuals complying with conventional antipsychotic treatment regimens derive little or no benefit in terms of symptom control or reduction, while another 30% gain only partial relief. 9 In a systematic review of the effects of chlorpromazine versus placebo, 4 it was confirmed that chlorpromazine was effective in reducing relapse over a period of 6 months-2 years and in improving global state (although placebo response rate was 40%); however, the drug was associated with sedation, acute movement disorders, parkinsonism, hypotension and weight gain. A systematic review of haloperidol versus placebo 5 confirmed that haloperidol was also effective in improving global state but was associated with dystonia, akathisia and parkinsonism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation